Acute toxicity of S-derivatives of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles - O. A. Suhak; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2017)
The urgency of the search for new biologically active compounds among the 1,2,4-triasole derivatives is beyond doubt. The promise of this direction has been confirmed by many publications by both domestic and foreign scientists. It is known that various derivatives of 1,2,4-triazole are low-toxic or practically non-toxic compounds, while possessing a wide range of biological effects. As we know, one of the main priorities of the introduction of new substances is a minor toxicity. Therefore, purposeful synthesis of low-toxic compounds and focused study of acute toxicity are the priority tasks of pharmacological research. The aim of the work was to study the acute toxicity of the first synthesized S-derivatives of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles. Materials and methods. An express method of V. B. Prozorovsky was selected for the study of acute toxicity. The basis of this method is the use of test substances in doses located on a logarithmic scale with an interval of 0.1, and all possible reliable LD50 results and their errors are calculated by pre-program of the probit analysis. Results. As a result of the studies, it was found that the acute toxicity of the synthesized compounds is within the limits of 193-770 mg/kg. According to K. K. Sidorov classification they are low-toxic or practically non-toxic compounds. The most toxic compound among thioles is 4-methyl-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol - 304 ± 65 mg/kg. The acute toxicity of N'-R1-iden-2-((4-methyl-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-ylthio)acetohydrazides are within the range of 193-770 mg/kg. Conclusions. The acute toxicity of 4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles S-derivatives is found to be within the range of 193-770 mg/kg. Some patterns of "structure-acute toxicity" are revealed.